3D printed modular origami inspired dielectrics for frequency tunable antennas - Wu, Y; Vallecchi, A; Yang, Y; You, Z; Stevens, C; Shamonina, E; Grant, PS (IEEE, 2019)
We explore the impact of origami structure meta-materials on electromagnetic devices. Here two modular origami-inspired dielectric structures were fabricated by 3D printing with the ability to shift the resonant frequency of patch antennas operating at approximately 1 GHz. Tunablity was achieved by deploying different dielectric origami configurations that were actuated to control the degree of folding or compression when placed on top of a standard patch antenna. The measured effects of the dielectric origami structure is to provide a 2% range of tunability of the antenna resonance frequency, with simulations showing a similar trend as experiments. The demonstration of active tuning by actuation of dielectric origami may find application in future antenna and telecommunication systems.